The Relationship Between Assertive Behavior and Academic Achievement of Biology Education Students: The Contribution of Assertive Behavior in Improving Academic Outcomes - Sri Yulianti; Joan S Awingan (Journal of Academic Biology and Biology Education, 2024)
Purpose of the study: The purpose of this study was to determine the level of assertive behavior of students in the Biology Education Department of UIN Alauddin Makassar, to describe students' learning achievements, and to analyze the relationship between assertive behavior and students' learning achievements in the department. Methodology: This study uses a quantitative approach with a correlational design. The tool used is a questionnaire to measure assertive behavior, with 42 statements covering three aspects. The data were analyzed using SPSS software with descriptive and inferential analysis techniques. The survey was conducted at Campuses I and II UIN Alauddin Makassar, involving 82 students of the Biology Education Department, batch 2022 and 2023 as samples. Main Findings: The average assertive behavior of Biology Education students is 115 with a standard deviation of 12.25, indicating heterogeneous data and a moderate tendency for assertive behavior. The average student learning achievement is 3.52 with a standard deviation of 0.16, indicating homogeneous data and very satisfactory learning achievement. There is a significant relationship between assertive behavior and learning achievement with a contribution of assertive behavior of 11%. Novelty/Originality of this study: This study revealed a significant relationship between assertive behavior and academic achievement of Biology Education students, with assertive behavior contributing 11%. This finding provides new insights into the role of assertive behavior in influencing academic outcomes, as well as increasing understanding of factors that can improve student achievement in higher education settings.